A educação em dois impérios: um estudo da obra de Machado de Assis e de Dostoiévski - Calabresi, Luis Henrique de Freitas (Universidade Federal de São Carlos, 2014)
This study aims at analyzing the existence of educational elements in common between Brazil and Russia during the 19th century through the reading of literary works by Machado de Assis and Fyodor Dostoevsky. Research publications in the area of History, in broader terms, and in the area of the History of Education, specifically, concerning these two countries and this period were used, as well as the literary criticism which can contribute to clarify historical connections in the literary works by our selected authors. Many aspects in common were found in the Brazilian and the Russian education in the 19th century, such as, for example, the educational institutions strong elitist emphasis, a connection between higher education and social prestige, and a critical perspective by Machado de Assis and Fyodor Dostoevsky towards the intense influx of European ideas and models in Brazil and in Russia in this period, among which we emphasize the educational aspects. Systematic education, brought from Europe to Brazil and Russia, were contradictory elements in these two countries. On the one hand the schooling initiatives were necessary to the modernizing processes in these societies. On the other hand, there was a series of social distortions and incompatibilities resulting from their adoption. Both of our selected authors maintained similar stances regarding this subject, focusing on criticism towards the adoption of European educational models in their countries.
Keywords: Educação - história; Literatura; Brasil; Rússia; History of Education; Literature; CIENCIAS HUMANAS::EDUCACAO